In the Fine Arts - The Genres of Interior, Landscape, Still Life and Portrait - Mahmudov Azizbek Odiljonovich (Research Parks Publishing LLC, 2021)
This article describes the formation and development of the historical genre in the fine arts of Uzbekistan from ancient times, the development of bench forms of the historical genre in the 30s of the 20th century, the incarnation of historical figures local artists B. Hamdamiy, A. Abdullayev, Sh. Hasanova and other works. The large-scale influx of local artists into the Uzbek fine arts in the 1950s and 1960s provided a variety of themes and styles for the historical genre. There have been reports that post-independence history, the past, and the growing interest in history have marked the rise of the historical genre.